Online-Based Intervention as an Effort to Increase Physical Activity Among Adolescent - Farhan Ardiansyah; Ferry Efendi; R.R. Dian Tristiana (Universitas STRADA Indonesia, 2024)
Background: Physical inactivity (PA) is an important contributor to morbidity and mortality globally. Adolescence is an important period of engaging in physical activity. 2 systematic reviews before 2022 concluded that studies need more methods and evaluations to prove the continued effect of Online-based interventions. It is therefore prudent to continue this research by considering how we can approach young people to grow healthy values into their day-to-day activities. Purpose: This study aims to determine online-based interventions for physical activity in adolescents. Method: A search of the literature databases Scopus, Science Direct and Springerlink using key words ‘Adolescents’, ’Teenagers’, ’E-health’, ’Internet-based’ , ‘Online-based’, and ’Physical Activity’ limited to 5 articles which fit the criteria for inclusion. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol was used, and papers were excluded if they were disease focused, not specific to adolescents or did not measure PA as an outcome. Results: All of studies had significant increases in PA as a result of an Online-Based intervention Studies include using various implementation mechanisms. The majority of studies use a mix of web- tutorials and based lessons for participants to work on in addition to goal setting via online, app-based (4/5). That remaining studies they were given an accelerometer as a measuring device and instructed online to perform the physical activity used for the rest of the study using online forums and PA experts to emphasize the effect of goal setting. Various intervention such as giving messages about PA or Health related issues were performed few a week for about 2-3 month. Conclusion: Online-based interventions are a very successful way to increase PA. More research is required to look at what theoretical principles are best to underpin interventions and also to assess the length of intervention required for optimal results after intervention. Ideas surrounding implementation require more studies to evidence base these interventions for schools, via intracurriculum or extracurriculum.